The implementation of the task-based approach in the teaching of english for specific purposes (ESP) with eleventh and twelfth graders from the productivity and quality, logistics and administration specialties at CTP Atenas 2016-2017 : a pedagogical approach = Implementación del enfoque basado en tareas en la enseñanza del inglés con propositos especificos con estudiantes de undécimo-dodécimo grado de las especialidades d eproductividad y calidad, y logística y distribución del CTP Atenas, 2016-2017: un enfoque pedagógico - González Porras, Jorge Andrés 1987-; Vásquez Carranza, Luz Marina ([San Ramón, Alajuela, Costa Rica], 2017)
This study reports on the effectiveness of the Task-Based Approach in the teaching of an English for Specific Purposes (ESP) course ata Public Technical High School in Costa Rica, 2016-2017. The case study used a mixed methodology, and it included 24 students ages 16-18 as well two male teachers ages 33-34. The participants were from the Logistics and Administra/ion, and Productivily and Quality specialties at Colegio Tecnico Profesional in Atenas. First, it was found that the Study Program proposed by MEP for the teaching of English in technical high schools does not truly constitute an ESP Program but an EGP Program. Second, there is a clear need to train English Teachers on the specialty they are to work on before they are assigned to teach these types of courses. A third finding was the relevance of using authentic materials as to ensure the success in the acquisition of ESP skills needed by students before they undergo a National Standardized Test or face a real-work situation in a near future; hence, teachers shall be trained on how to prepare and select the most appropriate materials to teach ESP in various sub- specialties. The effectiveness in using the Task-Based Approach to teach ESP is supported in that, students from the experimental group increased their performance by 20% when contrasting their grades obtained in the a pre- and post-ESP test. Similarly, the results revealed that those students who were taught using the Task Based Approach have a marked improvement of 20.6% regarding General English Knowldege as compared to the grades obtained by the students from the control group (only a 1.08%). The study constitutes a point of reference for MEP authorities to improve the Study Programs for the teaching of ESP at public high schools throughout Costa Rica, given the positive results found.
Proyecto de graduación (licenciatura en enseñanza del inglés)--Universidad de Costa Rica. Sede Occidente. Departamento de Filosofia, Artes y Letras. Sección de Lenguas Modernas, 2017
Keywords: INGLES -- ESTUDIO Y ENSEÑANZA; INGLES -- PLANES DE ESTUDIO; INGLES -- METODOS DE ENSEÑANZA; ACTIVIDADES CREATIVAS Y TRABAJO DE CLASE; EDUCACIÓN TÉCNICA -- COSTA RICA; ADQUISICION DE UNA SEGUNDA LENGUA